Development of a Manual Book Problem Tracking Model to Identify Student Learning Motivation - Pangestie, Esty Pan; Fendahapsari, Fendahapsari; Sukarningsi, Susi (Suluh: Jurnal Bimbingan dan Konseling, 2023)
Adolescence is a transitional period of development and growth faced by children aged 15/16 years due to various physical, social, and emotional changes, all of which will cause anxiety and discomfort. This period is also known as a period full of storms and pressure because teenagers must learn to adapt and accept all the changes that often cause emotional upheaval. If the activities carried out by adolescents with their peers are inadequate to meet the demands of their energy fluctuations, adolescents often release their excess energy in a negative direction. This activity can happen because the environment is often not following inner desires or expectations, so a person feels disappointed due to an imbalance between expectations and reality. Therefore, individuals in their teenage years, especially early adolescents, need adjustments to these changes in tasks and roles so that adolescents feel that the environment accepts them and can adapt well to situations of environmental expectations. As a Guidance and counseling teacher, you have to properly guide early youth so that they have a directed future. So, the purpose of this study is: 1) to know the various behaviors of early adolescents. 2) knowing the factors behind early adolescent behavior. 3) to know the counseling teacher's role in guiding early adolescents' behavior. In this qualitative research method, all existing data were analyzed using interviews, observation, and documentation.